2021
DOI: 10.1038/s41598-021-95046-y
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of oxidized LDL receptor-1 in intravascular thrombosis in a severe influenza mouse model

Abstract: Although coagulation abnormalities, including microvascular thrombosis, are thought to contribute to tissue injury and single- or multiple-organ dysfunction in severe influenza, the detailed mechanisms have yet been clarified. This study evaluated influenza-associated abnormal blood coagulation utilizing a severe influenza mouse model. After infecting C57BL/6 male mice with intranasal applications of 500 plaque-forming units of influenza virus A/Puerto Rico/8/34 (H1N1; PR8), an elevated serum level of prothrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…This notion is supported by a previous report showing the involvement of not the virus itself but neutrophil extracellular traps (NETs) in vasculitis in the lung using the hamster COVID-19 model [25]. Recently, our group reported a critical role of LOX-1 in thrombin generation and lung thrombosis in a severe influenza mouse model [17]. As previously observed in mice infected with the influenza virus, the induction of the Olr1 gene was also detected in the lungs, liver, and aorta of hamsters after SARS-CoV-2 infection in this study.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…This notion is supported by a previous report showing the involvement of not the virus itself but neutrophil extracellular traps (NETs) in vasculitis in the lung using the hamster COVID-19 model [25]. Recently, our group reported a critical role of LOX-1 in thrombin generation and lung thrombosis in a severe influenza mouse model [17]. As previously observed in mice infected with the influenza virus, the induction of the Olr1 gene was also detected in the lungs, liver, and aorta of hamsters after SARS-CoV-2 infection in this study.…”
Section: Discussionsupporting
confidence: 60%
“…In addition, immunohistochemistry demonstrated that LOX-1 increased in the bronchial epithelial and vascular endothelium of the lungs after infection with SARS-CoV-2. Given that the influenza-associated lung thrombosis did not occur in Olr1 knockout mice [17], it is possible that LOX-1 is also involved in promoting the thrombus formation in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virus infection and sample collection were performed as previously reported 13 , 15 . PR8 virus at 50 or 500 plaque-forming units (PFU) in 50 µL phosphate-buffered saline (PBS) or PBS only (control) were intranasally inoculated into mice under inhalation anesthesia with isoflurane.…”
Section: Methodsmentioning
confidence: 99%
“…The ssRNA virus influenza virus A (H1N1) is hypothesized to cause thrombosis, leading to multipleorgan dysfunction [137]. A study by Ohno et al [137] showed that during a severe influenza infection in a mouse model, thrombin generation is increased and LOX-1 expression in the aorta is upregulated in contrast LOX-1 in Infectious Diseases and Inflammation to LOX-1 knockout mice. It was suggested that LOX-1 is involved in the early thrombus formation in severe influenza infections.…”
Section: Virusmentioning
confidence: 99%